Analysis of gene expression in monocytes of immunized pigs after infection with homologous or heterologous African swine fever virus - Kholod, Natalia; Koltsov, Andrey; Koltsova, Galina (Frontiers in Veterinary Science, 2022)
African swine fever is a deadly disease of pigs caused by the large DNA virus (ASFV). Despite intensive research, little is known about the molecular mechanisms of ASFV pathogenesis. Transcriptome analysis of host and viral genes in infected macrophages revealed changes in expression of genes involved in various biological processes, including immune response, inflammatory response and apoptosis. To understand the mechanisms of virus pathogenesis, we used transcriptome analysis to identify the differences in gene expression between peripheral blood monocytes (PBMCs) isolated from pigs immunized with attenuated Congo ASFV strain (KK262), and then infected in vitro with virulent homologous Congo strain (K49) or heterologous Mozambique strain (M78). We found that overexpression of IFN-γ was detected only in cells infected with M78, although the expression of interferon-stimulated genes was increased in both types of cells. In addition, up-regulation of pro-inflammatory cytokines and chemokines was found in PBMCs infected with the heterologous strain M78, in contrast to the cells infected with K49. These data may indicate the beginning of an early immune response in cells infected with a heterologous, but not homologous strain. Transcriptome analysis revealed down-regulation of genes involved in endocytosis and phagocytosis in cells infected with the K49 strain, but not in PBMCs infected with M78. On the contrary, we detected activation of endoplasmic reticulum stress response genes in cells infected with a homologous strain, but not in cells infected with a heterologous strain. This study is the first attempt to determine the differences in the response to ASF infection between homologous and heterologous strains at the cellular level. Our results showed that not only genes of the immune response, but also genes involved in endocytosis and cellular stress response may be important for the formation of cross-protective immunity. This data may be useful for vaccine development or testing of candidate vaccines.